2017
DOI: 10.4273/ijvss.9.2.09
|View full text |Cite
|
Sign up to set email alerts
|

Aided System for Visually Impaired People in Bus Transport using Intel Galileo Gen-2: Technical Note

Abstract: Outwardly impeded individuals experience issues in travel and getting to data about open transportation frameworks. A few frameworks have been created for encouraging outwardly hindered utilizing the city transport. Most frameworks give double way correspondence and require expensive and complex hardware. The objective of this work is to decrease the troubles confronted by outwardly debilitated individuals while boarding in city transports, utilizing an intuitive remote correspondence framework. The framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Using an 11-level symmetric inverter with fewer switches and a 15-level asymmetric inverter with 15 levels, [7] experimentally validate the behaviour of the suggested topology. A series connection can be made between several sub-multilevel inverters, as shown in [8].…”
Section: Literature Surveymentioning
confidence: 87%
“…Using an 11-level symmetric inverter with fewer switches and a 15-level asymmetric inverter with 15 levels, [7] experimentally validate the behaviour of the suggested topology. A series connection can be made between several sub-multilevel inverters, as shown in [8].…”
Section: Literature Surveymentioning
confidence: 87%
“…Chen et al [14] found that visually challenged people frequently face action and identification difficulties in their daily lives. This study presents a smart wearable device with image recognition capabilities.…”
Section: Literature Surveymentioning
confidence: 99%
“…Finally, we will discuss the implications and challenges of implementing blockchain-based security measures in the IoT landscape. While blockchain holds great promise in fortifying IoT security, there are considerations such as interoperability, energy consumption, and regulatory aspects that must be carefully addressed [15].…”
Section: Introductionmentioning
confidence: 99%